The Effects of Isolation Pile on the Ground Deformation due to a Deep Pit Excavation - Guiping Nie; Ying Liu; Peilin Lv; Shaokun Ma; Zheng Chen; Xusheng He (Advances in Materials Science and Engineering)
Pit excavation could inevitably introduce ground movement and threaten the safety of nearby existing high buildings, metro tunnels, or roads. To reduce ground movement and protect those existing structures against large deformation, isolation pile is widely used in engineering practices. A series of physical model tests was carried out to investigate the effects of isolation piles on the ground deformation induced by excavating a pit. Digital image correlation (DIC) analysis was employed to study the ground deformation and slip surface under different pile lengths and locations relative to the retaining wall. The results indicate that the ground deformation and the shear band in the ground are less affected by the existence of a pile if the isolation pile’s end is above or slightly extends beyond the slip surface. In contrast, if the isolation pile extends beyond the slip surface sufficiently, even though the ground movement behind the pile is reduced, the settlement of the soil between the pile and retaining wall would be enlarged. Meanwhile, the horizontal deformation shows an arching shape along the depths and has a noticeable value in the middle section of subsoil. The ground deformation behind the isolation pile shows dependence on the pile’s horizontal displacement, regardless of the pile’s length and location. An empirical model is proposed to evaluate the efficiency of isolation piles on settlement protection. The comparison of the prediction and the results from tests and FEA shows a reasonable agreement.